Evaluation of operations in the hospitality industry - Safronov, Kirill; Martínez, Felipe; Pernica, Karel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This Bachelor's thesis provides an analytical exploration of bar operations in Prague's city center, aiming to identify potential enhancements in service delivery. Employing a mixed-methods approach that balances quantitative data with qualitative reviews, the study meticulously dissects elements such as quality, speed, flexibility, dependability, and cost within the hospitality industry. The evaluators, frequent patrons of the bars, offered granular insights into various attributes such as beverage selection, service professionalism, ambiance, and pricing strategies. By synthesizing this evaluator feedback with comprehensive observational data, the thesis presents tailored improvement strategies for each establishment, contributing both to academic literature on operations management and practical guidance for service optimization in the bar industry.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses